Knowledge, attitude, and practice regarding dengue vaccine: a baseline study of community members and health providers in Indonesia - Abdul Wahab; Ida Safitri Laksanawati; Retna Siwi Padmawati; Asal Wahyuni Erlin Mulyadi; Wahyu Triadmajani; Jarir At Thobari (Clinical and Experimental Pediatrics)
Background Despite recent behavioral interventions aimed at reducing the burden of dengue, persistent unfavorable related behaviors in the Indonesian community suggest that vaccination could be effective. However, before this is implemented nationally, public perception and acceptance of the vaccine should be assessed in addition to health providers’ points of view. Purpose This study aimed to assess the knowledge, attitudes, and practices (KAP) of community members and health providers in Indonesia. Methods A cross-sectional survey was conducted in 6 districts of 3 Indonesian provinces. Respondents included both community members and health providers living within the territory of the selected primary health care centers. Pretested questionnaires were used to gather information on the sociodemographic characteristics and KAPs regarding dengue vaccines. An independent t test was performed to compare the mean KAP scores between community members and health providers, while a logistic regression analysis was used to identify the predictors in each domain. Results Only 18.5% of health providers possessed high knowledge of the dengue vaccine versus only 12.5% of community members. Approximately one-third of the health providers versus one-fourth of community members displayed a high to moderate score for attitudes about dengue vaccines. Dengue vaccination practices demonstrated a more favorable score for both health providers and community members at 59.1% and 41.1%, respectively. No individual sociodemographic characteristics were associated with KAPs; rather, only education was correlated with better dengue vaccination practices. We also found that good knowledge of dengue was the only factor associated with all domains. Conclusion Our findings highlight the urgent need to deliver educational interventions to health providers and community members in Indonesia to improve their awareness of dengue vaccines.